2016
DOI: 10.1179/2046905515y.0000000055
|View full text |Cite
|
Sign up to set email alerts
|

Kidney injury owing to Streptococcus pneumoniae infection in critically ill infants and children: report of four cases

Abstract: Streptococcus pneumoniae sepsis has high morbidity, particularly if complicated by renal injury. Four patients with S. pneumonia invasive infections complicated by renal disorders are presented. The first case was an 18-month-old girl with pneumococcal empyema complicated by haemolytic uraemic (HUS) syndrome. She made a full recovery after mechanical ventilation, inotropic support and haemodiafiltration. The second was a 4-year-old boy who presented with acute post-infectious glomerulonephritis associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Kidney injuries derived from S. pneumoniae infections range from proteinuria to acute kidney failure ( 48 , 49 ). The clinical Sp-HUS strain mediated endothelial damage ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney injuries derived from S. pneumoniae infections range from proteinuria to acute kidney failure ( 48 , 49 ). The clinical Sp-HUS strain mediated endothelial damage ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified pathologic differences between a S. pneumoniae HUS strain and a WT strain with regard to their extracellular vesicles (EVs). Kidney injuries derived from S. pneumoniae infections range from proteinuria to acute kidney failure (50,51). The clinical Sp-HUS strain mediated endothelial damage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney injuries derived from S. pneumoniae infections range from proteinuria to acute kidney failure(50, 51). The clinical Sp-HUS strain mediated endothelial damage ( Fig.…”
Section: Discussionmentioning
confidence: 99%